2009
DOI: 10.1016/j.molcel.2009.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Silencing of the RASSF1A Tumor Suppressor Gene through HOXB3-Mediated Induction of DNMT3B Expression

Abstract: SUMMARY The RASSF1A tumor suppressor gene is epigenetically silenced in a variety of cancers. Here we perform a genome-wide human shRNA screen and find that epigenetic silencing of RASSF1A requires the homeobox protein HOXB3. We show that HOXB3 binds to the DNA methyltransferase DNMT3B gene and increases its expression. DNMT3B, in turn, is recruited to the RASSF1A promoter, resulting in hypermethylation and silencing of RASSF1A expression. DNMT3B recruitment is facilitated through interactions with Polycomb re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(133 citation statements)
references
References 46 publications
(55 reference statements)
5
120
1
5
Order By: Relevance
“…3B). On the basis of the wide range of cellular functions associated with HIC1 and RassF1A (16,19,24), it was not surprising to observe global changes in the MSC methylome. Furthermore, as both HIC1 and RassF1A were reported to function as TSGs that act via p53, we conducted unsupervised ontological analysis of the array target loci and found that p53 and its associated signaling components were significantly altered by me_H&R transfection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3B). On the basis of the wide range of cellular functions associated with HIC1 and RassF1A (16,19,24), it was not surprising to observe global changes in the MSC methylome. Furthermore, as both HIC1 and RassF1A were reported to function as TSGs that act via p53, we conducted unsupervised ontological analysis of the array target loci and found that p53 and its associated signaling components were significantly altered by me_H&R transfection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RASSF1A promoter is frequently hypermethylated in a variety of cancers, including lung carcinoma (Dammann et al, 2000(Dammann et al, , 2001(Dammann et al, , 2005Honorio et al, 2001), and its hypermethylation leads to epigenetic silencing of RASSF1A by HOXB3-mediated induction of DNMT3B expression (Palakurthy et al, 2009). APC is a negative regulator of Wingless-INT (WNT) pathway, which involves in selfrenewal of stem cell (Mazieres et al, 2005), and APC methylation occurrence rate is up to 94% in NSCLC but 20% in normal control group (Brabender et al, 2001).…”
Section: Hypermethylation and Hypomethylation In Lung Cancermentioning
confidence: 99%
“…-579 G>T is a single SNP in the promoter region of the DNMT3B gene, which may modify susceptibility to tumors (18,19). DNMT3Bs are the predominant expression forms of DNMT3B in human lung cancer and, in part, are involved in the epigenetic silencing of RASSF1A (20). DNMT3B proteins were highly expressed in a coordinate manner in lung tumors, particularly in smokers, and overexpression may result in promoter hypermethylation of multiple tumor suppressor genes (TSGs), ultimately leading to lung tumorigenesis and poor prognosis (21).…”
Section: Introductionmentioning
confidence: 99%